2017
DOI: 10.3389/fmicb.2017.01812
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Differences of Bacterial Metabolome and Microbiome in the Colon between Landrace and Meihua Piglets

Abstract: This study was conducted to compare the microbiome and metabolome differences in the colon lumen from two pig breeds with different genetic backgrounds. Fourteen weaned piglets at 30 days of age, including seven Landrace piglets (a lean-type pig breed with a fast growth rate) and seven Meihua piglets (a fatty-type Chinese local pig breed with a slow growth rate), were fed the same diets for 35 days. Untargeted metabolomics analyses showed that a total of 401 metabolites differed between Landrace and Meihua. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…Diet treatments here might have effects on colonic bile acid pro les characterized by a signi cant reduction in several bile acid pro les in ChB group as compared to control group. These results here were partly in line with a previous result that a lower amount of bile acids was associated with higher butyrate concentration in the porcine colon [40]. Accumulating evidence showed that abnormally higher levels of free bile acids in the colon, would disrupt colonic epithelial barrier integrity and cause epithelial cells oxidative stress and apoptosis, leading to gut dysfunction [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…Diet treatments here might have effects on colonic bile acid pro les characterized by a signi cant reduction in several bile acid pro les in ChB group as compared to control group. These results here were partly in line with a previous result that a lower amount of bile acids was associated with higher butyrate concentration in the porcine colon [40]. Accumulating evidence showed that abnormally higher levels of free bile acids in the colon, would disrupt colonic epithelial barrier integrity and cause epithelial cells oxidative stress and apoptosis, leading to gut dysfunction [41,42].…”
Section: Discussionsupporting
confidence: 92%
“…We have provided correlations between the abundance of microbial phyla and genera and specific rumen metabolites (Belanche et al, 2019), in an attempt to provide a functional context to changes in the rumen microbial population; however, in general, these approaches have been limited to a small range of welldefined rumen metabolites. Metabolomic techniques to describe a potentially wider range of metabolites have been used to study the link between gut microbiomes and the metabolome in several gut ecosystems (Dougal et al, 2012;Yan et al, 2017). In rumen-based studies, metabolomics has been used to investigate the effect of diet (O'Callaghan et al, 2018;Yang et al, 2018) to link the host genotype to efficient phenotypes in growing cattle (Artegoitia et al, 2017); the main aim has been to help to elucidate the effects of early-life nutritional interventions on rumen function (Abecia et al, 2018) and to understand the effect of plant extracts on rumen function (Wang et al, 2019).…”
Section: The Rumen Metabolomementioning
confidence: 99%
“…56 Specifically, accumulation of SCFAs and secondary bile acids was found to be higher in the colon lumen of Landrace piglets. 57 Moreover, a comparative study showed that Jinhua pigs exhibited better growth performance, lower diarrhea rates, and lower immune activation in response to challenge with an enterotoxigenic E. coli (ETEC) K88 species compared to Landrace pigs. The Landrace pigs also had a higher overall proportion of Lactobacilli spp., as well as a higher ratio of Lactobacilli to E. coli, and more tight junction proteins.…”
Section: Geneticsmentioning
confidence: 99%